Kilka uwag na temat majątku rodzinnego - Telusiewicz, Piotr (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostęne wyłącznie w języku angielskim: Polish legislation gives various definitions of the family, adjusting each of tchem to a specific regulation by law. The lack of uniformity in this field leads to inability to clarify and specify the disputable issues concerning the essence of the family and its functioning. This problem concerns the matter of family property, whose subjective and objective range cannot be defined and where rules of practice cannot be applied. It is necessary to say that trappings of family property present in Family and Protective Code provide the necessary basis for a discussion on the subject.